Study of traditional folk foods from the point of view of nutrition in Hajdú-Bihar County - Fejes, Veronika; Győri, Zoltán; Bardócz, Zsuzsa (Acta Agraria Debreceniensis, 2010)
Healthy nutrition is one of the major topics of our days. The occurrence of the so called “civilization diseases” is increasing continuously as a result of the changes in our nutritional habits and life-style. It was thought that folk nutrition at the beginning of the 19. Century had several beneficial effects on health. For this reason it was decided to study the food and nutritional habits of the population of Hajdu-Bihar County around the 1930s on thebasis of literary sources to see how well they do match with modern requirements of healthy nutrition.